The Hypertension Paradox: Survival Benefit After ST-Elevation Myocardial Infarction in Patients With History of Hypertension. A Prospective Cohort- and Risk-Analysis - Hoffmann, Fabian; Fassbender, Patricia; Zander, Wilhelm; Ulbrich, Lisa; Kuhr, Kathrin; Adler, Christoph; Halbach, Marcel; Reuter, Hannes (Frontiers in Cardiovascular Medicine, 2022)
Background: Mortality after ST-elevation myocardial infarction (STEMI) is dependent from best-medical treatment after initial event. Objectives: Determining the impact of prescription of guideline-recommended therapy after STEMI in two cohorts, patients with and without history of arterial hypertension, on survival. Methods: 1025 patients of the Cologne Infarction Model registry with invasively adjudicated STEMI were dichotomized according to their history of arterial hypertension. We recorded prescription rates and dosing of RAS-inhibitors, β-blockers and statins in all patients. The primary outcome was all-cause death. Mean follow-up was 2.5 years. Results: Mean age was 64±13 years, 246 (25%) were women. 749 (76%) patients had a history of hypertension. All-cause mortality was 24.2%, 30-day and 1-year mortality was 11.3% and 16.6%, respectively. History of hypertension correlated with lower mortality (hazard ratio [HR], @30 days: 0.41 [0.27-0.62], @1 year: 0.37 [0.26-0.53]). After adjusting for age, sex, Killip-class, diabetes mellitus, body-mass index, kidney function and statin prescription at discharge 1-year mortality HR was 0.24 (0.12-0.48). At discharge, prescription rates for RAS-inhibitors, β-blockers and statins, as well as individual dosing and long-term persistence of RAS-inhibitors were higher in patients with history of hypertension. On the same lines, prescription rates for RAS-inhibitors, β-blockers and statins at discharge correlated significantly with lower mortality regardless of history of hypertension. Conclusion: Patients with history of hypertension show higher penetration of guideline recommended drug therapy after STEMI, which may contribute to better survival. Better tolerance of β-blockers and RAS-inhibitors in patients with history of hypertension, not hypertension itself, likely explains these differences in prescription and dosing.